Friction: Friction of Ionic Liquid–Glycol Ether Mixtures at Titanium Interfaces: Negative Load Dependence (Adv. Mater. Interfaces 14/2018). Issue 14 (23rd July 2018) - An, Rong; Zhou, Guobing; Zhu, Yudan; Zhu, Wei; Huang, Liangliang; Shah, Faiz Ullah
Abstract : Structural reorientation of alkyl chains in the phosphonium cation of orthoborate ionic liquid mixed with glycol ether occurs with increasing normal load of the AFM tip. The flat reoriented structure, similar to the 'blooming lotus leaf', produces a new sliding interface that is responsible for the observed lower friction at higher loads. This work is reported by Rong An, Liangliang Huang, Faiz Ullah Shah and co‐workers in article number1800263 .